TINJAUAN HUKUM ISLAM TERHADAP TRANSAKSI JUAL BELI BUAH PEPAYA CALIFORNIA DI POHON - Muh. Irwan.T; Rahman Ambo Masse; Wawan M. (Universitas Islam Negeri Mataram, 2023)
This type of research uses a type of qualitative research. The data sources used are the population and samples, then the data collection technique is carried out by means of observation, interviews and documentation. The results showed that the practice of buying and selling California papayas on trees that occurred in Duampanua Village was a transaction that was often carried out by the community when California papayas were ready to be harvested. The reason farmers buy and sell is because it is considered practical The mechanism for evaluating the buying and selling of fruit on the tree is carried out by means of farmers and buyers alike appraising the fruit on the tree after estimating the amount of the harvest then determining the price There are two methods of determining the price, namely paying cash and paying after harvest while the implementation of the Ijab and Kabul is carried out orally in Islamic economics the practice of buying and selling fruit on trees is included in the practice of buying and selling fruit which is halal. Considering that the practice of buying and selling fruit on trees in Duampanua Village, Andreapi Polewali Mandar District, the fruit has been seen and there is also a contract system which has been agreed upon in the contract where the farmer's tree will change hands within a period of several months according to the agreed contract.